Crosstalk Between Intestinal Serotonergic System and Pattern Recognition Receptors on the Microbiota–Gut–Brain Axis - Layunta, Elena; Buey, Berta; Mesonero, Jose Emilio; Latorre, Eva (Frontiers in Endocrinology, 2021)
Disruption of the microbiota-gut-brain axis results in a wide range of pathologies that affect from the brain to the intestine. Gut hormones released by enteroendocrine cells to the gastrointestinal tract are important signaling molecules within this axis. In the search for the language that allows microbiota to communicate with the gut and the brain, serotonin seems to be the most important mediator. In recent years, serotonin has emerged as a key neurotransmitter in the gut-brain-axis since it controls completely both gastrointestinal and brain physiology. In addition, intestinal microbiota would be crucial in serotonin signaling, which gives more relevance to the role of the serotonin as an important mediator in the microbiota-host interactions. Despite the numerous investigations focused on the gut-brain-axis and the pathologies associated, little is known regarding how serotonin can mediate in the microbiota-gut-brain-axis. In this review, we will mainly discuss the serotonergic system modulation by microbiota as a pathway of communication between intestinal microbes and the body on the microbiota-gut-brain axis and explore novel therapeutic approaches for gastrointestinal diseases and mental disorders.